(untitled) (Experimental biology, 2026)
The article presents the structural features of the roach population in the Kapchagay Reservoir (age composition, size weight indicators, sex composition) based on ichthyological studies in 2024. The length of these captured individuals ranged from 89 to 323 mm and averaged 193 mm. Weight varied from 11 to 622 g with an average of 163 g. The roach was, in fact, two to eight years of age, but most were four to six years old. Size structure analysis showed the modal length size classes of 150–209 mm and 200–249 mm to be most common and weight size classes of 120–179 g and 180–239 g to be most common. The high frequency of roach catches in the scientific nets (30 mm mesh) supports these findings. In recent years, we have been observing positive trends concerning the structural characteristics of the roach population in the reservoir. Catches were studied and showed an increase in the roach from spring to autumn. The interpolation method was used to analyze its seasonal spatial distribution, which is the population. In spring, roach was overwhelmingly located in the right bank water area of the reservoir; in summer and autumn, nearly all were in the river mouth region of the left bank. In these regions, this distribution pattern is probably influenced by food resource availability and different abiotic factors.